Linear analysis of equations of process treatment metals - Švitra, Donatas; Janutėnienė, Jolanta (Lietuvos matematikos rinkinys, 1998)
Linear analysis of equations describing treatment process of metals by cutting iš presented. The analysis is based method on D-expansion method. There is choose a areas of asymptotically stability as well as areas describing harmful autooscillations arising during the treatment of metals by cutting is discussed.